Unveiling the Rose-colored Filter: Young Chinese Women’s Reflection of Romantic Chinese Dramas’ Influences on Their Romantic Ideals and Relationships - Si, Elva (Tufts Archival Research Center, 2020)
In the Chinese media context, sweet love television dramas, as an emerging branch of traditional romantic dramas, gradually gained popularity with their relatable romantic stories, simple character relationships, and low barrier for viewership. Based on a survey of 67 participants and seven follow-up one-on-one interviews, this study investigated how young Chinese women (18 to 22 years old) perceive sweet love dramas’ influences on their romantic ideals and relationships. Advisor: Julie Dobrow, Ph.D.